Student Challenges and Effective Strategies in Everyday Mathematics Learning for Junior High School Students - Wa Ode Indrawati; La Ode Ahmad Jazuli; La Arapu; Muhammad Ihwal; Dian Ulfa Sari (FKIP Universitas Halu Oleo, 2024)
Mathematics learning often faces various obstacles that affect the effectiveness and quality of education. Mathematical concepts are often abstract and difficult for students to understand without a clear and applicable explanation. As a result, students can feel confused and unable to master mathematical concepts with practical applications, hindering understanding and application of the material. The objectives of this research is to find out the students' description of the challenges and effective strategies in daily learning mathematics. This type of research is a qualitative description. Data collection is carried out through interviews, observations, or other methods, and then the data is analyzed in depth to find patterns, themes and meanings that emerge. The research instruments were interviews and questionnaires. The research results show that students prefer mathematics subjects compared to other subjects, only achieving a percentage score of 53%. Of course this is a challenge for a teacher. To overcome these challenges, several strategies that are considered effective in learning mathematics are the use of active learning methods, technology integration; differentiation approach, and development of problem solving skills..